Prospek Pembuatan Pakan Ayam Dari Bahan Baku Lokal (Contoh Kasus Gorontalo) - Akhadiarto, Sindu (Jurnal Sains dan Teknologi Indonesia, 2015)
Currently chicken feedÃ¢â‚¬â„¢sÃ‚Â price continues to rise, therefore a lot of chicken farmers suffered since the cost spent for feed could reach up to 70% of the total businessÃ¢â‚¬â„¢ cost. Most farmers still depend on the manufactured feed in, which the ingredients are imported.Ã‚Â Due to the increase of feed ingredientsÃ¢â‚¬â„¢Ã‚Â price in the international market (e.g. corn, soy, fish powder), the manufactured feed price also increase. To overcome the high price of manufactured feed, the local society should be equipped with the technology to produce local feed using local ingredients. The feed equipment will be made and adapted to the local conditions. The feed preparation technique is computerized using the feeding program "FeedStaR" which was made by BPPT in Indonesian language. By producing the feed independently, the result to be achieved, that is: feed at a low price, but still meet the nutritional requirements of the chickens. Gorontalo province is an area with potential overflowed corn, rice, coconut plantation and marine fisheries. However its breeding sector, especially chickens, is less able to develop due to the high price of manufactured feed. With the development and wide scale of agriculture, plantation and fisheries in Gorontalo, the chicken feed production is highly prospective to be developed.Saat ini harga pakan ayam terus meningkat, sehingga banyak peternak yang rugi, karena biaya pakan bisa mencapai 70% dari biaya usaha. Sebagian besar peternak, pakannya masih tergantung pada pakan pabrik dengan bahan baku yang masih impor. Dengan naiknya harga bahan baku pakan di pasaran Internasional (jagung, kedelai, tepung ikan), mengakibatkan harga pakan pabrik ikut naik. Untuk mengatasi mahalnya harga pakan buatan pabrik, maka masyarakat didaerah perlu dibekali teknologi pembuatan pakan lokal yang bahan bakunya berasal dari daerah setempat. Peralatan pakan dibuat dan disesuaikan dengan kondisi daerah tersebut. Teknik penyusunan pakan dilakukan secara komputerisasi dengan program pakanÃ‚Â Ã¢â‚¬Å“FeedStaRÃ¢â‚¬ÂÃ‚Â yang telah dibuat BPPT dalam bahasa Indonesia. Dengan pembuatan pakan sendiri, maka hasil yang ingin dicapai adalah : pakan dengan harga murah, namun tetap memenuhi syarat nutrisi ayam. Provinsi Gorontalo merupakan daerah dengan potensi tanaman jagung, padi, perkebunan kelapa dan hasil perikanan laut yang melimpah. Namun bidang peternakan, khususnya ayam kurang bisa berkembang, karena mahalnya harga pakan pakan (pabrik). Dengan semakin meningkat dan luasnya hasil pertanian, perkebunan dan perikanan di Gorontalo, maka pembuatan pakan sangat prospektif untuk dikembangkan.Keywords:Ã‚Â Native chickens, local ingredients, feed, nutrient